The Bad Guys in Mission unpluckable - Blabey, Aaron (Blabey, Aaron. Bad guys, 2017)
Still yearning to be seen as heroes, Wolf, Shark, Snake, and Piranha set out to rescue ten thousand chickens from a high-tech cage farm--but one unexpected problem is Mr. Snake himself, also known as "The Chicken Swallower."